2017
DOI: 10.7567/jjap.56.07jc06
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of contact force and amount of hair between skin and bone-conducted sound transducer using electrical impedance

Abstract: Noninvasive bone-conducted hearing aids require the consistent fitting of transducers for consistent hearing. In this paper, a method of estimating the contact force and amount of hair between a person’s skin and a bone-conducted sound transducer using electrical impedance is proposed. Experiments are conducted with a human surface model consisting of hair, skin, and bone. The estimator is implemented with a three-layered neural network. Ten measurements for 70 conditions are conducted by changing the contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As shown in these figures, four peaks of the electrical impedance from I to IV were confirmed; such peaks were also confirmed from the results of the human head model in previous research. 40) As the contact force changes, the peaks of the electrical impedance also change. Figure 5(b) shows a typical example of the change in electrical impedance.…”
Section: Experiments 1: Validation Of the Relationship Between The Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in these figures, four peaks of the electrical impedance from I to IV were confirmed; such peaks were also confirmed from the results of the human head model in previous research. 40) As the contact force changes, the peaks of the electrical impedance also change. Figure 5(b) shows a typical example of the change in electrical impedance.…”
Section: Experiments 1: Validation Of the Relationship Between The Co...mentioning
confidence: 99%
“…We have validated the relationship between the contact force and the electrical impedance using a human model, 39) and proposed a method of estimating the contact force from the electrical impedance. 40) However, the results were obtained only from the human model, and measurements with human subjects have not been discussed. A preliminary experiment showed that human subjects show similar trends to the human model.…”
Section: Introductionmentioning
confidence: 99%
“…We propose a method that uses the electrical impedance of the transducer [36][37][38] to solve this problem of contact force estimation. The electrical impedance of the transducer shows a characteristic change according to the contact force.…”
Section: Introductionmentioning
confidence: 99%